ANALISIS MUTU DAN PENDUGAAN UMUR SIMPAN PENYEDAP RASA JAMUR TIRAM PUTIH - Andi Maryam; Sinta Sinta (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2019)
Oyster mushroom productivity that is too high can cause difficulties in cultivation. The rainy season with high humidity causes the growth of oyster mushrooms to be very rapid, so there is a tendency to harvest. Oyster mushrooms cannot be stored for long, either at room temperature or in the refrigerator. This study aims to determine the quality of oyster mushroom flavoring including color, texture, and taste based on shelf life and percentage of water content. This study processed white oyster mushrooms with variations in drying temperatures of 50oC and 55oC using a completely randomized design with two treatments and three repetitions. The best percentage of water content is flavoring with 50oC temperature treatment, which is 6.027%, the quality of the flavor enhancer in terms of color, texture, aroma, and taste does not decrease with a shelf life of up to 8 weeks.